Primary omental haemangiopericytoma. (24th May 2011) - Morris-Stiff, Gareth; Falk, Gavin A; Joyce, Daniel; Rubin, Brian; Chalikonda, Sricharan
Abstract : Haemangiopericytomas arise from Zimmermann's pericytes, which regulate the blood flow through capillaries. Given their cell of origin, haemangiopericytomas may arise anywhere; however, the most common locations are the lower limb musculature, the pelvic fossa and the retroperitoneum. A comprehensive review of the English literature has revealed only 19 previous confirmed haemangiopericytomas arising from omentum, the case reported herein being the 20th.